If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5q = -3q + 10 Reorder the terms: -5q = 10 + -3q Solving -5q = 10 + -3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '3q' to each side of the equation. -5q + 3q = 10 + -3q + 3q Combine like terms: -5q + 3q = -2q -2q = 10 + -3q + 3q Combine like terms: -3q + 3q = 0 -2q = 10 + 0 -2q = 10 Divide each side by '-2'. q = -5 Simplifying q = -5
| 52x^2+13=0 | | 2x-4+x=28 | | 24=-8u+5(u+6) | | 2x^2+2y^2-2xy-2x+4y+5=0 | | 3x^2+27x-6.5=0 | | 8(x-3)+9=5x+3(-4+x) | | 15-27=2(21) | | 5w=6w+7 | | .65x+18.50=.75x+18.50 | | 5s+8t=70 | | 6x^3-x^2-27x-20=0 | | (-81)/(+9)= | | n^2+3n-12-6=0 | | 2x^2-5x^2+5x-2=0 | | 0.01x+3.97=2.04x-2.12 | | -2x+4-2x=12 | | -2b+7=11 | | n^2+7n+15-5=0 | | (3u^2)-u-10=0 | | 200-25p=0 | | x(1.8+x)=.19 | | -5(x+1)+14=-3x+1 | | 3iz-z(1+i)-4i=0 | | 9x-16-3x=26 | | y^2-5y-x+9=0 | | t^2=5r | | 5x-2x+x= | | 4(2x-3)=3+8-11 | | 4a+5(-2a-3)-a=-1 | | 2+3[4+3(11+3)+2]+5= | | .75x+18.50=.65+18.50 | | -6y+6=-2y(4y+6) |